Culture under cross-examination : international justice and the special court for Sierra Leone - Kelsall, Tim, 1970- (Cambridge, UK ; New York : Cambridge University Press, 2009)
"The international community created the Special Court for Sierra Leone to prosecute those who bore the greatest responsibility for crimes committed during the country's devastating civil war. Tim Kelsall examines some of the challenges posed by the fact that the Court operated in a largely unfamiliar culture, in which the way local people thought about rights, agency and truth-telling sometimes differed radically from the way international lawyers think about these things. By applying an anthro-political perspective to the trials, he unveils a variety of ethical, epistemological, jurisprudential and procedural problems, arguing that although touted as a promising hybrid, the Court failed in crucial ways to adapt to the local culture concerned. Culture matters, and international justice requires a more dialogical, multicultural approach"--Provided by publisher.
White man's justice? : Sierra Leone and the expanding project of international law -- The story of the CDF trial -- An unconventional army : chains of command in a patrimonial society -- Facts, metaphysics and mysticism : magical powers and the law -- We cannot accept any cultural consideration : the child soldiers charge -- "He's not very forthright" : finding the facts in a culture of secrecy -- Cultural issues in the RUF, AFRC and Charles Taylor trials -- Conclusion : from legal imperialism to dialogics.
Includes bibliographical references (pages 268-284) and index.
Keywords: Special Court for Sierra Leone; Special Court for Sierra Leone; Special Court for Sierra Leone; International criminal courts -- Netherlands; International criminal courts -- Sierra Leone; War crime trials -- Social aspects -- Sierra Leone; War crime trials -- Social aspects -- Netherlands; LAW -- Criminal Law -- General; International criminal courts; War crime trials -- Social aspects; Netherlands; Sierra Leone